Vpliv izvedenca na izid postopka - Šugman Stubbs, Katja (Podjetje in delo, 2014)
The article points out the importance of proper distinction between the competences of the court and the expert witness in legal proceedings. It is becoming more and more common that the judge bases his or her opinion almost exclusively on an expert's opinion. There are numerous reasons for this: either the judge is not doing his or her job properly and decides to include an expert too soon, but frequently the reason is in a dependence on different technologies to solve the legal problem and their quick development which disables a judge to properly understand the technological or scientific question at hand. Science presents itself as a direct pathway to the truth, seeming irrefutable and objective. The author points out that the judges have a duty to critically examine all the elements of the experts' work: from evidence gathering to the methods use and the way the findings are presented. At the end of the day, it is the judge who has to take full responsibility for the outcome of the case.
Keywords: izvedenstvo; pravna zmota; sodišča; sodni postopek